Influence of water repellent chemical additive and different curing regimes on dimensional stability and strength of earth bricks from termite mound-clay - Akinyemi, Banjo A. (Heliyon, 2019)
This article is focussed on evaluating the effects of water repellent admixture and different curing regimes on characteristics of clay from termite hills used for production of earth bricks. Water absorption, thickness swelling and compressive strength characteristics of the specimens with different compositions of cement, hydrated lime and water repellent additive subjected to different curing regimes were measured. The samples were characterised by SEM and FTIR. The least water absorption was at 3.3% while thickness swelling ranged from 0.78 to 3.21 % for the samples. Saturated curing condition resulted in an average compressive strength of 35.5 N/mm(2), cured curing recorded an average value of 32.9 N/mm(2) while dry curing condition produced an average compressive strength of 26.9 N/mm(2) and the wet curing condition resulted in 25 N/mm(2). SEM characterisation of sample containing 70% termite soil, 30% cement and 0.05 Hydropruf indicated fewer voids, regular and smooth appearance in comparison with others. FTIR analysis showed distinctive broad bands at wave numbers of 3439 cm(−1) for O-H stretching, and 1033.83–1008.80 cm(−1) for O–H bending for all samples tested. The best performing composition in terms of the dimensional stability test was 70% termite mound clay, 10% cement, 20% hydrated lime and 0.05 Hydropruf additive. The highest mechanical strength was from composition of 70% termite mound clay, 30% cement, no hydrated lime and 0.05 Hydropruf additive. It is concluded that saturated and cured method showed better performance than the wet and dry curing regimes. The termite secretions similarly improved the clay composition in conjunction with cement, lime and chemical admixture in the internal structure of the bricks.